Effects of therapeutic climbing in healthcare and rehabilitation: A systematic review protocol - Bastien Delhoste; Fadl Moudni; Asiya Parvin Allaudeen; Bruno Chenuel; Edem Allado (PLoS ONE, 2025)
Background Climbing is a fast-growing physical activity around the world. From recreational activity to sport, more and more people are practicing. Initially used in the treatment of psychiatric and psychological disorders, climbing’s scope of application has expanded to include orthopedic, pediatric and neurological rehabilitation. Nowadays, it is a therapeutic tool used by many physical and psychological rehabilitation professionals. The aim of this coming systematic review is to determine the therapeutic effects of climbing for promoting physical activity in healthcare and rehabilitation. We will identify the pathologies for which this tool is available, and relate the climbing protocols used to the effects obtained (tool performance and undesirable effects). Methods and analysis We will include studies in which the effects of climbing or bouldering, used as a therapeutic tool, have been studied. The literature search will be conducted until 20 July 2025 using the databases MEDLINE, EMBASE, The Cochrane Library, Web of Science, and EBSCO. Following PRISMA guidelines, three reviewers in two groups will carry out all tasks: screening, selection and data extraction. The two groups of reviewers will assess each study’s risk of bias using ROB-2 for randomized clinical trial (RCTs), ROBINS-I for non-randomized clinical trial (CT) and the Joanna Briggs Institute Critical Appraisal tools for use in Systematic Reviews for case of reports/series and non-controlled clinical trials. Disagreement will be resolved by discussion until the reviewers reach consensus. Strenghts and limitations of the study One of the strengths of this study is the description of the protocols used in the therapeutic climbing sessions, which has not been much reported until now. The analysis of the therapeutic effects on different dimensions is also a strength of this study. The main limitation of the study is that the results are likely to be biased according to the heterogeneity of the patients, protocols and measurement tools used in the selected studies.